INTELLECTUAL CAPITAL - INTANGIBLE ASSETS MATERIALISED IN THE MAIN ENGINE OF THE NATIONS' ECONOMIC RECOVERY - Laura-Maria, Dindire; Silvia, Dugan (Strategii Manageriale, 2013)
The research developed in this paper is mainly aimed at the achievement of certain analyses on some key variables of intellectual capital in companies from EU countries and thus, implicitly, from Romania, as well as through the Pearson correlation matrix, intensity analysis of the relationships between the respective variables of the three dimensions related to the intellectual capital, namely the human capital, the structural and relational capital and the GDP/capita. The main research techniques used for the research were: investigation of secondary data and content analysis of the major reports of international organisations on intellectual capital, as well as statistical methods of analysis and interpretation of data, respectively descriptive statistics and correlations. The main results of the research consist in identifying the main directions that envisage the area of intellectual capital in which companies must act to diminish the negative effects of the economic crisis.